Exploring perspectives of Dscam for cognitive deficits: a review of multifunction for regulating neural wiring in homeostasis - Yinyi Xiong; Li Li; Xiaorong Zhang (Frontiers in Molecular Neuroscience)
Down syndrome cell adhesion molecule (Dscam) represents a group of cell surface transmembrane receptors with a conserved protein structure across species. In Drosophila, Dscam exhibits extensive isoform diversity resulting from alternative splicing, providing each cell with a unique identity. Identical isoforms expressing on the surfaces of opposing cells mediate homophilic interactions, thereby driving intracellular signaling for establishment of complex neuronal branching patterns. Mammalian Dscam lacks isoform diversity but retains the homophilic binding property. In contrast, it is capable of mediating multifaced neurological functions which are more complex than those of Drosophila Dscam. In this review, we spotlight that the homeostatic mechanisms mediated by Dscam are significant for normal cognitive function. Down syndrome (DS) and autism spectrum disorders (ASD) are two common neurodevelopmental diseases, the cognitive deficits of which are frequently correlated with aberrant DSCAM expression. Previous studies have presented some evidence that the neural homeostatic mechanisms associated with DSCAM are compromised in these two diseases. However, the insight into DSCAM-mediated homeostatic plasticity remains seriously overlooked. Furthermore, recent studies put forward that DSCAM might be one of the key molecules involved in neuronal age-related mechanisms during early stage of Alzheimer’s disease (AD), a neurodegenerative disease linked to aberrant homeostatic mechanisms. In this review, we aim to provide a comprehensive understanding of Dscam-mediated crucial roles in regulating neural circuitry for homeostasis, thus elucidating how Dscam induces changes of homeostatic plasticity to affect cognitive function in either physiological or pathological conditions. We hope this review could inspire future studies to test the extent to which Dscam-mediated neural homeostatic mechanisms contribute to neurological disorders accompanied by cognitive deficits, thus facilitating research on discovering potential therapeutic avenues.